PENGARUH KETERAMPILAN PROSES SAINS (KPS) TERHADAP HASIL BELAJAR FISIKA SISWA MELALUI METODE EKSPERIMEN DENGAN PENDEKATAN INKUIRI TERBIMBING - syafriyansyah _; Eko Suyanto; I Dewa Putu Nyeneng (Jurnal Pembelajaran Fisika, 2013)
The objectives of this research are to find out: 1) the influence of science process skill (or KPS) to student’s physic learning results through experiment method with guided inquiry approach; 2) experiment method effectiveness with guided inquiry approach in training/developing student’s science process skill indicated by unimproved student’s learning results. This was a quasi experiment and conducted in State Senior High School 1 in Punduh Pidada in Pesawaran regency. Population was all students of grade X in State Senior High School 1 in Punduh Pidada. Samples were students in classroom X1 and were selected with purposive sampling technique. Data were collected with test method and non test method (observation) by using pretest and posttest learning results and observation sheets of science process skill. This research used simple linier regression test and t-test for analysis, where the requirement test used normality and linearity tests. The results showed that t-count was higher than t-table (4.169 2.035), so that Ho that stated that there was no any influence between science process skills to the student’s physic learning results through experiment method with guided inquiry approach was rejected. It meant that there was a significant influence of science process skill to student’s physic learning results through experiment method with guided inquiry approach. R Square analysis derived a very significant influence (36.7%). In addition, experiment method with guided inquiry approach was very effective in training/developing science process skill as well as improving student’s learning results (cognitive domain). The proof was 79% improvement percentage of average student’s learning results.Keywords: science process skill, experiment method, and guided inquiry